Reassessing the fuelwood situation in developing countries - Arnold, J.E.M.; Persson, R. (2003)
Analysis of the fuelwood situation has been hampered by lack of reliable information, and has been the subject of considerable debate. The present paper assesses the implications of recent information on the subject. New data and recent more accurate projections show that increasing urbanisation and rising incomes lead to fuelwood users shifting to charcoal and other fuels. The rate of increase in fuelwood use is slowing down and in some areas consumption is now in decline. In contrast, charcoal use is growing strongly and is becoming a much larger part of the woodfuels total in some regions. In general, the new information supports arguments that fuelwood use seldom requires major interventions to maintain or augment supplies, though in some areas charcoal may. However, though woodfuels may be less of a concern to the security of the forest estate than was previously feared, huge numbers of people continue to rely on woodfuels as a source of energy or income, and will continue to do so. The review argues that these linkages constitute a larger component of the contribution that forestry can make to poverty alleviation than appears to be currently reflected in most forestry and agroforestry policies and programmes. Areas that could need attention in order to address such neglect are discussed.